2020
DOI: 10.3390/biom10040576
|View full text |Cite
|
Sign up to set email alerts
|

Uric Acid Has Direct Proinflammatory Effects on Human Macrophages by Increasing Proinflammatory Mediators and Bacterial Phagocytosis Probably via URAT1

Abstract: The relationship of uric acid with macrophages has not been fully elucidated. We investigated the effect of uric acid on the proinflammatory ability of human macrophages and then examined the possible molecular mechanism involved. Primary human monocytes were differentiated into macrophages for subsequent exposure to 0, 0.23, 0.45, or 0.9 mmol/L uric acid for 12 h, in the presence or absence of 1 mmol/L probenecid. Flow cytometry was used to measure proinflammatory marker production and phagocytic activity tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 50 publications
2
18
0
Order By: Relevance
“…aureus by blood neutrophils, instead downregulating the content of rodshaped neutrophils, monocytes and natural killers in the blood. Our findings are consistent with data from Martínez-Reyes CP et al [27], which showed in vitro that incubation of human macrophages for 12 hours in the presence of increasing concentrations of uric acid (0,23; 0,45 and 0,9 mM/L, ie comparable to its level in plasma) dose-dependently increased their phagocytic activity, which was defined as the percentage of macrophages containing labeled Escherichia coli. This was accompanied by increased expression of TL4-receptors and increased production of TNF-α.…”
Section: Discussionsupporting
confidence: 93%
“…aureus by blood neutrophils, instead downregulating the content of rodshaped neutrophils, monocytes and natural killers in the blood. Our findings are consistent with data from Martínez-Reyes CP et al [27], which showed in vitro that incubation of human macrophages for 12 hours in the presence of increasing concentrations of uric acid (0,23; 0,45 and 0,9 mM/L, ie comparable to its level in plasma) dose-dependently increased their phagocytic activity, which was defined as the percentage of macrophages containing labeled Escherichia coli. This was accompanied by increased expression of TL4-receptors and increased production of TNF-α.…”
Section: Discussionsupporting
confidence: 93%
“…The UA increase observed in CKD patients seems to favor OS through the inhibition of nicotinamide adenine dinucleotide phosphate (NADPH) oxidase, altering the vascular response to nitric oxide [ 61 ]. Furthermore, it seems to exert a pro-inflammatory action by activating transcription of the factor nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kB) [ 62 ] and stimulating the synthesis of tumor necrosis factor (TNF)-α and IL-1 [ 63 ]. We hypothesized that the UA reduction observed in our patients after 9 weeks of SYN consumption, may be due to two probable mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperuricemia could induce an activated status of inflammation [ 51 ] or autoinflammation [ 52 ]. It could instigate inflammation by stimulating the production of inflammatory factors such as interleukin-6, interleukin-1(beta), tumor necrosis factor-alpha and CRP [ 53 ], or enhancing reactive oxygen species [ 54 ], or initiating systemic inflammation via the nuclear factor (NF)- κB signaling pathway [ 55 ], or direct proinflammatory effects on macrophages [ 56 ]. Intra-articular injection of MSU-induced inflammatory arthritis could result from UA injection [ 57 ].…”
Section: Distinct Reaction and Priming Pathways Of Inflammation Bymentioning
confidence: 99%